Influence of heat exchange on magnetic susceptiblility of lanthanum cobaltates - Kozlovskii, A.A.; Khirnyi, V.F.; Deineka, T.G. (Functional Materials, 2006)
An influence of thermal processes rate on temperature dependence of complex magnetic susceptibility x = x' — ix" in ceramic perovskites La₁₋ₓSrₓCoO₃ (x = 0.15; 0.25; 0.35) has been studied. At increasing cooling rate, the x value grew up as compared to the value obtained under slow (equilibrium) temperature variation. This effect is explained by thermomagnetic component (∂M/∂T)(∂T / ∂t) of x value, which is due to strong dependence of magnetization M on temperature T near the Curie point.